2013
DOI: 10.1155/2013/592429
|View full text |Cite
|
Sign up to set email alerts
|

Study of Flowering Pattern in Setaria viridis, a Proposed Model Species for C4 Photosynthesis Research

Abstract: Green foxtail millet (Setaria viridis) has NADP-ME type of C4 photosynthesis. Because of its short life cycle, small genome size of ∼515 Mb, small plant stature, high number of seed set, simple growth requirements, and wide adaptability, this diploid (2 = 18) weed is proposed to be a model species for the study of C4 photosynthesis. It is also a representative of bioenergy grasses and a model for genetic study of invasive weeds. Despite having all traits of a model species, it is difficult to cross-pollinate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…To ensure that this was not due to differences between the classifiers, we evaluated the calls of the InceptionV3cnn classifier of the first and last image in the light, which confirmed that of the flowers identified as opened during the night. This observation is in agreement with a previous report that flower opening is predominantly restricted to the nighttime hours in S. viridis (Rizal et al, 2013 ). Further evaluation of the specific period in the night when the highest rate of TAA occurs indicates unique temporal differences between the varieties (Figure 5 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…To ensure that this was not due to differences between the classifiers, we evaluated the calls of the InceptionV3cnn classifier of the first and last image in the light, which confirmed that of the flowers identified as opened during the night. This observation is in agreement with a previous report that flower opening is predominantly restricted to the nighttime hours in S. viridis (Rizal et al, 2013 ). Further evaluation of the specific period in the night when the highest rate of TAA occurs indicates unique temporal differences between the varieties (Figure 5 ).…”
Section: Resultssupporting
confidence: 94%
“…In a study that developed a crossing method for the common lab variety of S viridis , A10, Jiang et al showed that TAA was primarily restricted to 1 h after dawn (Jiang et al, 2013 ). Another study analyzed TAA in the A10 variety, imaging of panicles at 1 min intervals over the course of 3 days and concluded that the majority of TAA in A10 takes place at night (Rizal et al, 2013 ). However, light and touch may induce flower opening (Kobayasi, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Panicles of Setaria species are protected by tough bristles that may trap potential microbial carriers like insects, air-borne particles and water droplets. However, colonization through open spikelets is limited by a narrow time frame, as anthesis happens only once per spikelet, lasts for short periods of time (60 min) and occurs only at night and when temperatures are low ( Rizal et al, 2013 ). Colonization of panicle endospheres may also occur through pollinators or injuries caused by phloem-feeding insects ( Aleklett et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of panicle endospheres may also occur through pollinators or injuries caused by phloem-feeding insects ( Aleklett et al, 2014 ). Although Setaria species are considered to be wind pollinated, Rizal et al (2013) showed that potential pollinators were attracted to panicle tissues just prior to anthesis. Furthermore, the presence of rOTUs classified as insect endosymbionts like Buchnera in our data set suggests that Setaria samples in this study once served as host for phloem-feeding aphids.…”
Section: Discussionmentioning
confidence: 99%
“…Weed-crop competition was also influenced by climatic conditions, since Setaria is a C4 species and wheat is a C3 crop. Arid features of experimental area (salinity, temperature, radiation and drought) favored Setaria germination and growth, as season long emergence of Setaria was noticeable (Rizal et al, 2013).…”
Section: Water Use Efficiency and Correlation Matrixmentioning
confidence: 96%